The peculiarity of the national style of performing folk songs (the Ukrainian «Rain is Falling» and the Chinese «Red Sunset») - Du Yuling (ХДАК, 2024)
Folk music is an important element of the cultural heritage of each nation. It accumulates historical experience, traditions, worldview and mentality, which is reflected in specific stylistic features of performance. The study of the features of the national style of performing songs of different nations allows us to identify the unique features of their musical culture, promotes intercultural dialogue and expands the horizons of ethnomusicological analysis. The Ukrainian folk song «The Rain is Falling» and the Chinese folk song «Red Sunset» are vivid examples that demonstrate the wealth of national musical traditions. The analysis of the selected works is important for understanding the nature of each culture through music.
Theoretical substantiation master's creative project to obtain a master's degree by the second (educational and professional) level of higher education majors: 025 Musical art
Keywords: вокальне виконавство; vocal performance; музична культура Китаю; музична культура України; народний спів український; народнопісенна творчість